Why worry about Intravenous (IV) therapy? - Asemi, S (Iran University of Medical Sciences, 1995)
IV Therapy is an important option in incapable patients' treatment. In this paper, we discuss about: A) For best control of them, we must know about what materials are in these drugs? B) For what reason they are use? C) What errors may be happen in use of them? Amount of IV fluids must be accommodating with loss of fluids. Firstly, we review amount of main body fluids. Main part of our body weight is fluid. 50-70% of our weight is water. Amount of water is varying in persons with different body weight. Because, lipid cellules are waterproof, when they are increase, amount of water is decrease. Body fluids are divided into two sections: intracellular fluids and extracellular fluids.